2009
DOI: 10.1002/gps.2305
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal sleep duration and cognitive impairment in a population‐based study of older adults

Abstract: Increases in sleep duration are associated with cognitive impairment. A biological explanation for this association is currently lacking. Increases in sleep duration could be a marker of cognitive deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 48 publications
6
79
2
1
Order By: Relevance
“…Loerbroks and Benito-León reported that increase in sleep duration is associated with cognitive impairment in older adults (Loerbroks et al 2010;BenitoLeón et al 2009). Our findings found no association between sleep durations and dementia and are thus inconsistent with these previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Loerbroks and Benito-León reported that increase in sleep duration is associated with cognitive impairment in older adults (Loerbroks et al 2010;BenitoLeón et al 2009). Our findings found no association between sleep durations and dementia and are thus inconsistent with these previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies reported that decreased sleep duration over time was associated with lower cognitive function [61,68,73] , and 4 studies found that increased sleep duration was related to worse cognition [59,61,68,73] . One of these studies included prospective data on cognitive function, enabling analyses of changes in sleep duration with cognitive decline; however, there was no indication of association in these results [73] .…”
Section: Results Of Studies On Change In Sleep Duration and Cognitivementioning
confidence: 99%
“…Most studies included both women and men [16, 50, 51, 54, 56-69, 71, 72, 74, 76-80] , although some studies focused on women only [55,70,73] or men only [53,75] ; 1 study did not specify the sex of participants [52] . Studies generally specified age thresholds for participants at the time of first cognitive interview: ≥ 30 years [50] , ≥ 45 years [80] , ≥ 50 years [74, 76,77] , ≥ 55 years [16] , ≥59 years [71], ≥ 60 years [54,58,60,65] , ≥ 65 years [55, 62-64, 66, 68, 69, 75] , ≥68 years [70], and ≥ 70 years [59,73,79] . Other studies provided the mean age [67] or age ranges [51-53, 56, 57, 61, 72, 78] of their participants, but did not explicitly describe an age threshold as part of the inclusion criteria; regardless, older adults were eligible for all studies.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing the full texts of the remaining 30 articles, 20 articles were excluded because of the following reasons: not relevant to our analysis ( n = 5) [14,17,[21][22][23], insufficient data ( n = 11) [12,15,16,[24][25][26][27][28][29][30][31] , shared an identical study population with other articles ( n = 1) [19], data from preexisting dementia [32] , using dementia mortality as a result [33] , and using an acute biomarker as exposure [34] . The remaining 10 studies (3 case-control studies [10,11,35] and 7 cohort studies [36][37][38][39][40][41][42] were included in the final analysis.…”
Section: Statistical Analysesmentioning
confidence: 99%